Behavioural strategy: Adaptability context - Piórkowska Katarzyna (Management, 2016)
The paper is embedded in the following fields: strategic management in terms of behavioural strategy concept, adaptability construct, and micro-foundations realm as well as organizational theory and psychology. Moreover, the paper concerns to some extent a multi-level approach in strategic management involving individual, team, and organizational level. The aim of the paper is to contribute to extend, on one hand, the ascertainment set in the field of behavioural strategy as behavioural strategy encompasses a mindboggling diversity of topics and methods and its conceptual unity has been hard to achieve (Powell, Lovallo, Fox 2011, p. 1371), and on the other hand, to order mixed approaches to adaptability especially to gain insights on micro-level adapting processes (individual adaptability and adaptive performance) in terms of the multi-level approach. The method that has been used is literature studies and the interference is mostly deductive. The structure of the manuscript is four-fold. The first part involves the considerations in the field of adaptability and adaptive performance at the individual level. The issues of adaptability and adaptive performance at the team level have been presented in the second part. The third part encompasses the organizational adaptability assertions. Finally, the conclusion, limitations of the considerations highlighted as well as the future research directions have been emphasized. The overarching key finding is that the behavioural strategy concept may constitute the boundary spanner in exploring and explaining adaptability phenomenon at different levels of analysis.